2014
DOI: 10.1002/art.38398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tocilizumab in Conventional Treatment–Refractory Adult‐Onset Still's Disease: Multicenter Retrospective Open‐Label Study of Thirty‐Four Patients

Abstract: Objective. Adult-onset Still's disease (AOSD) is frequently refractory to standard therapy. Tocilizumab (TCZ) has demonstrated efficacy in single cases and in small series of patients with AOSD. The aim of this multicenter study was to assess the efficacy of TCZ in patients with AOSD refractory to conventional treatment.Methods. This was a retrospective open-label study of TCZ treatment in 34 patients with AOSD who had experienced an inadequate response to corticosteroids and at least 1 standard synthetic immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 13 publications
(31 reference statements)
0
62
1
2
Order By: Relevance
“…However, there was no significant difference in potency of tocilizumab monotherapy with or without MTX in RA patients [83]. In addition to targeting RA, the anti-IL-6 approach has also been used to treat patients with other autoimmune diseases such as juvenile idiopathic arthritis [84] and adult-onset Still's disease [85]. …”
Section: Page 26 Of 64mentioning
confidence: 98%
“…However, there was no significant difference in potency of tocilizumab monotherapy with or without MTX in RA patients [83]. In addition to targeting RA, the anti-IL-6 approach has also been used to treat patients with other autoimmune diseases such as juvenile idiopathic arthritis [84] and adult-onset Still's disease [85]. …”
Section: Page 26 Of 64mentioning
confidence: 98%
“…More familiar to rheumatologists and internists is the use of TCZ in adult-onset Still's disease (AOSD), particularly in patients who are refractory to conventional therapies and present a predominant polyarticular pattern of the disease [14][15][16]. AOSD is a rare multisystem inflammatory disease of unknown origin that is included within the clinical spectrum of autoinflammatory disorders [16,17].…”
Section: The Role Of Tocilizumab In Systemic Autoimmune and Inflammatmentioning
confidence: 99%
“…No published prospective clinical trials evaluating TCZ in AOSD are available, but promising efficacy results have been observed in several case reports and retrospective analyses [84][85][86][87]. Improvements in clinical (fever, rash, and myalgia) and laboratory (ESR and CRP) manifestations were observed after treatment with TCZ in a review of 24 cases of AOSD in Korean patients [88].…”
Section: Other Diseasesmentioning
confidence: 99%